A Study Of Female Social Status In In The Works “Jane Eyre” By Charlotte Bronte And “Anna Karenina” By Leo Tolstoy (Zien Journal of Social Sciences and Humanities, 2025)
This study investigates the portrayal of female social status in Jane Eyre by Charlotte Brontë and Anna Karenina by Leo Tolstoy. By analyzing the two central female characters, the paper highlights how literature reflects the societal norms and constraints placed on women in Victorian England and 19th-century Russia. The findings reveal a shared struggle for identity, independence, and societal acceptance, despite cultural differences. Through a comparative literary analysis, the study aims to understand how gender, class, and morality shape women's roles in these canonical novels.